Bud Rot of Palm - Monica L. Elliott (EDIS, 2012)
To understand bud rots, an explanation of palm anatomy is necessary. The growing point of the palm is often called the bud or heart. All leaves originate from there, and each palm stem has only one. Thus, when the bud is damaged or diseased, the palm usually dies. The first symptom is discoloration and wilting of the spear leaf and wilting/discoloration of the next youngest leaf. This revised 4-page fact sheet was written by Monica L. Elliott and published by the UF Department of Plant Pathology, July 2012.